Molecular phylogeny of trees species in Tripa Peat Swamp Forest, Aceh, Indonesia inferred by 5.8S nuclear gen - ZAIRIN THOMY; ARDHANA YULISMA; ESSY HARNELLY; ARIDA SUSILOWATI (Biodiversitas Journal of Biological Diversity, 2018)
Authors. 2018. Molecular phylogeny of trees species in Tripa Peat Swamp Forest, Aceh, Indonesia inferred by 5.8S nuclear gen. Biodiversitas 19: 1186-1193. Tripa peat swamp forest is protected areas that have high biodiversity. Nevertheless, in some areas, the damage occurred due to conversions of land function to oil palm plantations. The impact of conversions of peat swamp forest to oil palm plantations has led to biodiversity decreased. Hence, it is important to identify the remain tree species in Tripa peat swamp forest. This study aimed to determinetrees species diversity in Tripa peat swamp forest by using of 5.8S rRNA nuclear gene. Research was conducted at Forest Genetics and Molecular Forestry Laboratory, Faculty of Forestry, IPB from September 2015 to August 2016. Molecular identification consisted of DNA extraction, PCR analysis, and sequencing. The data were analyzed using Bioedit, MEGA 6, BLAST, and ITS2 database. Molecular identification using ITS 1 and ITS 4 primer successfully amplified (the ITS region ITS1-5.8S-ITS2) of 16 trees species from 9 families. BLAST analysis results indicate the presence of 16 species has similar bases sequence with the GeneBank DNA database. The plant species are Branckenridgea palustris (Ochnaceae), Gonystylus sp. (Thymelaeaceae), Tristaniopsis whiteana (Myrtaceae), Syzygium sp.1 (Myrtaceae), Macaranga triloba (Euphorbiaceae), Syzygium garciniifolium (Myrtaceae), Knema intermedia (Myristicaceae), Palaquium ridleyi (Sapotaceae), Palaquium sp. (Sapotaceae), Dyera lowii (Apocynaceae), Elaeocarpus petiolatus (Elaeocarpaceae), Ficus sp. (Moraceae), Syzygium leptostemon (Myrtaceae), Chilocarpus suaveolens (Apocynaceae), Alstonia pneumatophora (Apocynaceae), and Alstonia sp. (Apocynaceae). Phylogeny tree reconstruction using the Neighbor-Joining Method (NJ) showed that 5.8S rRNA nuclear gene was successful as marker for 16 trees species from 9 different families. In addition, the 5.8S also successful for resolving phylogenetic relationships at genus level i.e. Alstonia, Palaquium, Syzygium, Tristaniopsis, Macaranga, Elaeocarpus, and Ficus.